VOCABULARY MASTERY BY USING FLASH CARD (An Experimental Study at Elementary Level Prima Putra English Course) - Dody Wahyudi Purnama (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2016)
Mastery of vocabulary is one of the obstacles that generally facing students in learning English. Mengingat guru sebagai fasilitator untuk siswa didiknya, maka seorang guru diharapkan dapat memilih media pembelajaran yang sesuai untuk anak sekolah dasar. Considering the teacher as a facilitator for student protege, then a teacher is expected to choose the appropriate learning media for primary school children. Vocabulary is basic knowledge to be able to learn all four language skills in English. The use of flash media cards at the elementary school level students can affect their memory, because the elementary school level students will easily remember to understand the vocabulary by using the media image. Thus the influence of media flash cards, would make students more active in the enrichment of vocabulary.